Chemical composition and in vitro antioxidant and antibacterial activity of Heracleum transcaucasicum and Heracleum anisactis roots essential oil - Torbati, Mohammadali (Tabriz University of Medical Sciences, 2014)

(untitled)
Introduction: In vitro antioxidant and antibacterial activity and volatile compositions of two Heracleum species (Apiaceae) including Heracleum transcaucasicum and Heracleum anisactis roots Essential Oil (EO) were investigated. Methods: The volatile compositions of EOs were analyzed by GC/Mass spectroscopy. To detect the antioxidant activity of essential oils TLC-bioautography and DPPH radical scavenging assay by spectrophotometry was performed. Additionally, the antibacterial activity of two essential oils were studied and compared against four pathogenic bacteria by agar disc diffusion method and MIC values of the EOs were determined using the broth dilution method. Results: Myristicin was the dominant component in both EOs. It was identified as 96.87% and 95.15% of the essential oil composition of H. transcaucasicum and H. anisactis roots, respectively. The TLC-bioautography showed antioxidant spots in both EOs and IC(50) of H. anisactis and H. transcaucasicum EO was found to be 54 μg × ml (-1) and 77 μg × ml (-1), respectively. Regarding the antimicrobial assay, H. anisactis EO exhibited weak to moderate antibacterial activity against gram-positive bacteria and also Escherichia coli, whereas the essential oil from H. transcaucasicum was inactive. Conclusion: Based on the results from this study, both tested EOs mainly consist of myristicin. Despite the presence of myristicin with known antibacterial property, the EO from H. transcacausicum showed no antibacterial activity. Thus it is supposed that the biological activity of plants is remarkably linked to the extracts’ chemical profile and intercomponents’ synergistic or antagonistic effect could play a crucial role in bioactivity of EOs and other plant extracts.